The Benefits of Consuming Sardines to Prevent Hypertension and Type 2 Diabetes Mellitus for Senior Citizens - Vallensia Nurdiana Febriyanti (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Along with the increasing number of senior citizens in Indonesia, the number of cases of non-communicable diseases (NCDs), especially hypertension and diabetes mellitus experience escalation too, which certainly will have a direct impact on human resource productivity, social and economic development. In addition, hypertension and type 2 diabetes mellitus are the causes of the highest mortality rates in Indonesia. This article aims to encourage the public especially the senior citizens to prevent hypertension and type 2 diabetes mellitus by consuming fish containing high omega 3, EPA, and DHA, such as sardines at least twice a week or the equivalent of 200-400 grams a week. In terms of the methods, a literature study approach was employed in elaborating the research topic. The findings of this study demonstrate that sardines contain anti-inflammatory, antioxidant roles, boost the membrane fluidity, boost the number of insulin receptors and insulin action, and also contain hypotensive and hypoglycemic effects. In this manner, sardines are highly proven to be able to effectively prevent type 2 diabetes mellitus, prevent hypertension, and lower blood pressure, especially for senior citizens.